Kualitas kelekatan santri anak-anak - KHOIRUDDIN, KHOIRUDDIN (Universitas Gadjah Mada, 2001)
Society is paying much more attention to pesantren, school of The Koran for children and youth, with its integrated education systems nowadays. But for children in the age of primary school (SD), could pesantren substitute the function of family in developing children’s quality of attachment? To answer that question, this research was conducted. The subject was taken by purposive technique consisted of 103 students of primary school, 110 students of school of The Koran for children and youth (pesantren campuran), and 72 students of school of The Koran for children (pesantren khusus anak) in the age of 1 1 - 13 years, fifth or sixth grade of primary schools of Bantu1 Yogyakarta and Magelang Central Java. The six kinds of scale were used to uncover children’s quality of attachment to parents, teachers (ustadz), friends and sensitivity of attachments’ figures: parents, teachers and friends. Questionnaire was used to uncover sex, type of primary education, and how long they stayed in pesantren. Ancova AB 4 covariable was used to analyze data. Qualitative procedure was used to learn more about psychological dynamic of children’s attachment. Results of the analyses showed that: 1. Pesantren, with its activities and educational interactions lasting all the time, could not substitute the function of family in developing children’s quality of attachment. A thesis that the communal unity of dormitory system in pesantren develop intimate solidarity and familiarity, among students themselves and between students and teachers (ustadz/kyai), did not have empirical verification in this research. 2. An attachment problem that students had gone through was more related to the lack of attachment figures’ sensitivities: parents, teachers, and fkiends. As a result, the longer students stayed in pesantren, the lower attachment quality they had. A thesis that the longer students stay in pesantren, the more they attach to the teachers and friends, did not have supporting data from the field. 3. The quality of attachment to parents, teachers, and friends had an important role to students’ achievement. The lower students’ attachment quality brought risk the worse their achievements. 4 . Difference fiom primary school students who had parents as the main attachment figures, pesantren’s students had no main attachment figures. The attachment quality to parents, teachers, and friends of pesantren’s students were relatively the same and not high enough.